Burden of mental illness: a review in an Indian context. Issue 4 (2nd October 2018) - Sahithya, B. R.; Reddy, R. P.
ABSTRACT: Mental disorders pose a major challenge to the community due to early onset, chronic progressively deteriorating course, frequent relapses and disability. They are associated with tremendous distress both for the patient and the caregiver, and can produce significant disability, especially when not treated in a timely manner. This review aims to discuss the burden of mental illness in terms of economic cost, family burden, disability and unemployment in India. After a conceptual overview of burden, barriers to mental health and treatment gaps are discussed. Finally, progress made in the area of mental health, recent government initiatives and future directions to address the growing problems associated with mental disorders are discussed.